Artificial electrochemically active biofilm for improved sensing performance and quickly devising of water quality early warning biosensors. (15th June 2021) - Qi, Xiang; Wang, Shuyi; Jiang, Yong; Liu, Panpan; Li, Qingcheng; Hao, Wen; Han, Jinbin; Zhou, Yuexi; Huang, Xia; Liang, Peng
Highlights: Artificial EAB shortens startup time of biosensor. High repeatability of biosensor can be obtained by using artificial EAB. Low concentration of electroactive bacteria improves biosensor's sensitivity. 1% of sodium alginate was optimum for sensitivity of artificial EAB. Artificial EAB realizes real-time online water quality early-warning. Abstract: A major challenge for devising an electrochemically active biofilm (EAB)-based biosensor for real-time water quality early-warning is the formation of EAB that requires several days to weeks. Besides the onerous and time-consuming preparation process, the naturally formed EABs are intensively concerned as they can hardly deliver repeatable electrical signals even at identical experimental conditions. To address these concerns, this study employed sodium alginate as immobilization agent to encapsulate Shewanella oneidensis MR-1 and prepared EAB for devising a biosensor in a short period of less than 1 h. The artificial EAB were found capable of delivering highly consistent electrical signals with each other when fed with the same samples. Morphology and bioelectrochemical properties of the artificial EAB were investigated to provide interpretations for these findings. Different concentrations of bacteria and alginate in forming the EAB were investigated for their effects on the biosensor's sensitivity. Results suggested that lower concentration of bacteria would be beneficial until it increased to 0.06 (OD660 ). Concentration of sodium alginate affected the sensitivity as well and 1% was found an optimum amount to serve in the formation of EAB. A long-term operation of the biosensor with artificial EAB for 110 h was performed. Clear warning signals for incoming toxicants were observed over random signal fluctuations. All results suggested that the artificial EAB electrode would support a rapid devised and highly sensitivity biosensor. Graphical abstract: Image, graphical abstract